Advances In Drug Delivery Systems, Challenges, And Future Directions: Navigating Emerging Trends For Enhanced Therapeutic Efficacy (Journal of Namibian Studies : History Politics Culture, 2022)
Recent advancements in molecular pharmacology and a better understanding of disease mechanisms have highlighted the importance of targeting specific cells involved in disease initiation and progression. This is particularly crucial for life-threatening diseases that require therapeutic agents with potential side effects, necessitating precise tissue targeting to minimize systemic exposure. Modern drug delivery systems (DDS) utilize cutting-edge technology to enhance systemic drug delivery to targeted sites, maximizing therapeutic effectiveness while reducing off-target accumulation in the body. These DDS play a vital role in disease management and treatment, offering significant advantages over traditional delivery systems in terms of performance, automation, precision, and efficacy. Comprised of nanomaterials or miniaturized devices with biocompatible, biodegradable, and highly viscoelastic components, these systems have an extended circulating half-life. This review provides a comprehensive overview of the history and technological progress of drug delivery systems, highlighting the latest advancements, therapeutic applications, challenges, and future directions for improved performance and utilization.